The prevalence of congenital anomalies in Iran: A Systematic Review and Meta-analysis - Morvarid Irani; Talat Khadivzadeh; Seyyed Mohsen Asghari Nekah; Hosein Ebrahimipour; Fatemeh Tara (Mashhad University of Medical Sciences, 2018)
Introduction: Congenital anomalies is one of most important causes of hospitalization, disability and neonatal death; the cost of admission and treatment of these children imposes a heavy burden on the health system and their families. Therefore, the present study was performed with aim to investigate the status of congenital anomalies in Iran through systematic review and meta-analysis. Methods: In this review for finding the related articles, the databases of SID, Iranmedx , Irandoc, Magiran ,Scopus, Pubmed and Google scholar were searched using the keywords such as Prevalence, Iran, Congenital anomalies in Persian and English journals from 1986 to 2018. Data were analyzed by meta-analysis method using random effects model. The heterogeneity of the studies was calculated by I2 Index. Results: Of 2306 studies, 35 studies which met the inclusion criteria from 1986 to 2018 entered to the meta-analysis. The results of this meta-analysis showed that the total prevalence of congenital anomalies in Iran is 2.6%. The prevalence of abnormalities in boys is 2.8% and in girls is 2%. Also, the most common congenital anomalies were skeletal abnormalities (29.1%) and genitourinary system abnormalities (23.2%), respectively. Conclusion: The results of this study indicate a high prevalence of congenital anomalies in Iran. Further studies are needed to more identify this issue and plan to prevent congenital anomalies.